Alberto Moravia Revisited: L’amore coniugale or the Couple in Distress - Capek-Habekovic, Romana (Spunti e Ricerche, 2016)
The aim of this article is twofold: to discuss the complex nature of the relationship between the two spouses in the novel, which is conditioned by their perception of reality and their own self-identity through roles they assume within their marriage; and secondly, to analyze Moravia’s ideas with regard to "il mestiere dello scrivere," which he interjects into the principal narration of the novel by employing intertextuality as a stylistic devise.